Islamic International Relations in the Study and Practice of Contemporary Diplomacy - Cecep Sobar Rochmat; Ratna Alfina Nurcahyani; Savira Maulida; Salsa Nabyla Ayu Firnanda (NAJAHA, 2025)
International relations are currently dominated by western paradigms and secular thinking that causes a separation between religious and world affairs in the life of social and political aspects. The purpose of this study is to identify the application of Islamization of Science in the study of International Relations at University of Darussalam Gontor based on the Islamic Worldview and reflect on the practice in the time of the Prophet and Caliph, to be implemented into the diplomatic aspects of the contemporary era. This research uses a qualitative approach with data collection techniques using library research. The result of this research is that it has been found that the International Relations study program at University of Darussalam Gontor has integrated Islamic Science with International Relations, with the application of Islamization of Science into the learning curriculum both in formal courses and with several routine Islamization study activities under the auspices of the Directorate of Islamization. Islamization is an urgency in itself to deny the understanding of secularism that has dominated all aspects of the discipline of International Relations, therefore, as a tamyiz academic community, we should always continue to support the Islamization of Contemporary Science movement, in order to gain an understanding of science based on haqiqi truth.